2011
DOI: 10.1091/mbc.e10-08-0717
|View full text |Cite
|
Sign up to set email alerts
|

Protein kinase Cδ regulates vaccinia-related kinase 1 in DNA damage–induced apoptosis

Abstract: A pro-apoptotic function of activated PKCδ may be mediated by several downstream nuclear regulators involved in apoptotic cell death. Vaccinia-related kinase 1 (VRK1) is a new nuclear target of PKCδ in the regulation of apoptotic cell death induced by DNA damage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 42 publications
0
13
0
1
Order By: Relevance
“…Immunoblotting analysis was performed as we previously described [30,31]. For immunoprecipitation, cell lysates were prepared in lysis buffer (20 mM Tris-HCl, pH 7.5, 150 mM NaCl, 1 mM EDTA, 1 mM EGTA, 1% Triton X-100, 2.5 mM sodium pyrophosphate, 1 mM β-glycerol phosphate, 10 μg/ml pepstatin A, 10 μg/ml leupeptin, 1 mM PMSF, 10 μg/ml aprotinin, 10 mM NaF, and 1 mM Na 3 VO 4 ).…”
Section: Immunoblotting and Immunoprecipitationmentioning
confidence: 99%
See 1 more Smart Citation
“…Immunoblotting analysis was performed as we previously described [30,31]. For immunoprecipitation, cell lysates were prepared in lysis buffer (20 mM Tris-HCl, pH 7.5, 150 mM NaCl, 1 mM EDTA, 1 mM EGTA, 1% Triton X-100, 2.5 mM sodium pyrophosphate, 1 mM β-glycerol phosphate, 10 μg/ml pepstatin A, 10 μg/ml leupeptin, 1 mM PMSF, 10 μg/ml aprotinin, 10 mM NaF, and 1 mM Na 3 VO 4 ).…”
Section: Immunoblotting and Immunoprecipitationmentioning
confidence: 99%
“…Recent studies identified the essential roles of the VRK family in cell signaling, nuclear envelope dynamics, histone modification, apoptosis, and cell stress responses [18,21,30,32]. Our previous studies demonstrated that VRK3 negatively regulates MAP kinase signaling by promoting the activity of the vaccinia H1-related (VHR) phosphatase, which specifically dephosphorylates and inactivates extracellular signal-regulated kinases (ERKs) in the nucleus [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…Because VRK1 phosphorylates p53 at Thr-18 (16 -18) and is also implicated in some DDR (18,22), we hypothesized that VRK1 might also be activated in early steps of cellular DDR. In this work, we determined whether VRK1 can be regulated by DNA damage as an indication of response to altered chromatin structure and determined its consequences on the response to DSBs detected by the formation of 53BP1 foci, a process that is independent of p53 (9).…”
Section: Activation Of Vrk1 By Dna Damage In Resting Cells-vrk1mentioning
confidence: 99%
“…Thr-18 phosphorylation plays a threshold role in p53 responses (17,21), and additional p53 phosphorylations contribute to the specificity of cofactor selection (20). VRK1, which can phosphorylate p53 (16), has been associated with later stages of the DDR and multiple effector mechanisms (18,22). Human VRK1 is required for entry in the cell cycle (23), and its loss causes a cell cycle arrest in G 0 (23).…”
mentioning
confidence: 99%
“…The quantities of proteins used in kinase assays were measured by using silver nitrate (Sigma-Aldrich) or immunoblotting. Immunoblot analysis was performed as we previously described elsewhere (Park et al, 2011). For immunoblot analysis, bands were visualized using the Western blot detection kit (Neuronex, Pohang, South Korea).…”
Section: Protein Kinase Assay and Immunoblottingmentioning
confidence: 99%